Hukum Waris terhadap Anak Adopsi dalam Perspektif Islam - Muhammad Lutfi Syarifuddin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2020)
In practice, in Indonesia children adoption has become a public phenomenon in society and is part of the family law system because it involves individual interests in the family. In the case of adoption, parents need to pay attention to the best interests of the child and be implemented based on local customs, applicable laws and regulations, this has been regulated in Article 39 of the Child Protection Act. Adoption of children is divided into two types, namely adoption of children between Indonesian citizens (domestic adoption) and adoption of Indonesian citizens by foreign citizens (adoption between countries). Appointment of children must be done by legal process, through the establishment or decision of the Court. The research method is normative juridical research. Based on the research results, the inheritance Indonesian citizens rights in the Indonesian inheritance law case are implemented based on Islamic law, adopted children do not inherit from adoptive parents and remain the biological parents. Under customary law, the inheritance of adopted children depends on customary law in the area. By law adoption children do not inherit from adoptive parents, and adopted children remain the heirs of their biological parents.